2011
DOI: 10.1177/1460408610396026
|View full text |Cite
|
Sign up to set email alerts
|

Fat embolism syndrome: What have we learned over the years?

Abstract: Although its original clinical description dates from the nineteenth century, fat embolism syndrome remains a diagnostic challenge for clinicians. Fat emboli occur in all patients with long-bone fractures, but only few of them develop a multisystem disorder affecting the lung, brain, and skin, also known as fat embolism syndrome (FES). The incidence of FES varies and is often underestimated. Mechanical and biochemical theories have been proposed for the pathophysiology of FES. Clinical manifestations consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 115 publications
(146 reference statements)
0
23
1
5
Order By: Relevance
“…Bed side echocardiography did not reveal cardiac failure. Applying modified Gurd'sand Wilson criteria 7,8 ( Table 1) for fat embolism syndrome(FES), it was found that present case satisfied 3 major criteria and 4 minor criteria required for diagnosis. On applying Schonfeld's criteria 9 (Table 2), which has more respiratory features, total scorewas 10 (> 5 is required for diagnosis of fat embolism syndrome).…”
Section: Case Reportmentioning
confidence: 84%
See 2 more Smart Citations
“…Bed side echocardiography did not reveal cardiac failure. Applying modified Gurd'sand Wilson criteria 7,8 ( Table 1) for fat embolism syndrome(FES), it was found that present case satisfied 3 major criteria and 4 minor criteria required for diagnosis. On applying Schonfeld's criteria 9 (Table 2), which has more respiratory features, total scorewas 10 (> 5 is required for diagnosis of fat embolism syndrome).…”
Section: Case Reportmentioning
confidence: 84%
“…There were also no evidence of injury or bleeding from any intra-abdominal site. Landmark work of Gurd and Wilson 3,11 provided diagnostic criteria for fat embolism syndrome, which has been subsequently modified 7,8 and applied to our patient. Diagnostic criteria given by Schonfeld's had score of 10, which further supported our diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinic criteria for diagnosing FES, but the most relevant in our case are Gurd and Wilson’s criteria established in 1974 ( Table 4 ). 4 , 5 An additional sign which is very specific for FES is a brain MRI showing multiple microemboli in the white matter. 6 Our patient had acute hypoxic respiratory failure requiring intubation, acute encephalopathy, fever 40 °C, sudden thrombocytopenia, tachycardia, and MRI of the brain revealed extensive punctate ischemic infarcts in the white matter of both hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…It has been adapted many times since then. Modified Gurd and Wilson's criteria[ 2 8 ] requires at least one major and at least four minor signs for diagnosis [ Table 1 ]. Schonfeld et al .,[ 9 ] incorporated assessment of oxygenation with ABG in their scoring system [ Table 2 ].…”
Section: Discussionmentioning
confidence: 99%